2018
DOI: 10.1016/j.seizure.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and predictive factors in post-stroke seizures: A retrospective case-control study

Abstract: The size of anterior infarction, presence of blood products within the infarct bed, and especially LN predicted PSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
4
13
2
1
Order By: Relevance
“…Our results support the findings of several smaller studies that did not find an increased number of acute symptomatic seizures in patients undergoing IVT 26,[28][29][30]32 . Some of these studies presented more clinical details of patients suffering from acute symptomatic seizures, but the overall numbers of patients with seizures were limited in most studies, ranging from n = 3 to n = 25.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results support the findings of several smaller studies that did not find an increased number of acute symptomatic seizures in patients undergoing IVT 26,[28][29][30]32 . Some of these studies presented more clinical details of patients suffering from acute symptomatic seizures, but the overall numbers of patients with seizures were limited in most studies, ranging from n = 3 to n = 25.…”
Section: Discussionsupporting
confidence: 92%
“…Frequencies of acute symptomatic seizures noted by us are similar to those in several other studies in patients who underwent recanalization treatments, ranging between 1.2 and 3.8% 25,29,31,32 , with only two studies that reported higher frequencies between 8.1 and 23.4% 26,30 . These discrepancies are probably due to differences in seizure detection, classification and a referral bias in single-center studies with populations from tertiary stroke-centers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Graham et al showed that the 10-year estimate of poststroke seizure recurrence from either total anterior circulation infarct, partial anterior circulation infarct, or posterior circulation infarct was 28.7%, 13.4%, and 4.8%, respectively [22]. Studies have found that ischemic strokes involving the cortex, especially those with hemorrhagic transformation, were at a higher risk of seizures [19, 2325]. Others have looked at such as NIH stroke scale (NIHSS), infarct size, and etiology of the ischemic stroke [17].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke merupakan penyebab kejang yang paling umum pada lansia. 9,10 Hasil penelitian ini didukung oleh penelitian Tanaka et al 11 yang melaporkan insiden kejang pasca stroke lebih tinggi pada pasien berusia <65 tahun dibandingkan 85 tahun ke atas. Faktor-faktor risiko yang diketahui berpe-ran pada usia <65 tahun untuk terjadinya kejang pasca stroke ialah hiponatremia, subtipe stroke hemoragik, konsumsi alkohol, keterlibatan kortikal, dan keparahan stroke.…”
Section: Pendahuluanunclassified